Child Neurology Education for Pediatric Residents: How Are We Doing?. (March 2017) - Albert, Dara V. F.; Patel, Anup D.; Behnam-Terneus, Maria; Sautu, Beatriz Cunill-De; Verbeck, Nicole; McQueen, Alisa; Fromme, H. Barrett; Mahan, John D.
The aim of this study was to evaluate whether the current state of child neurology education during pediatric residency provides adequate preparation for pediatric practice. A survey was sent to recent graduates from 3 pediatric residency programs to assess graduate experience, perceived level of competence, and desire for further education in child neurology. Responses from generalists versus subspecialists were compared. The response rate was 32%, half in general pediatric practice. Only 22% feel very confident in approaching patients with neurologic problems. This may represent the best-case scenario as graduates from these programs had required neurology experiences, whereas review of Accreditation Council of Graduate Medical Education–accredited residency curricula revealed that the majority of residencies do not. Pediatric neurologic problems are common, and pediatric residency graduates do encounter such problems in practice. The majority of pediatricians report some degree of confidence; however, some clear areas for improvement are apparent.